(untitled) (Práxis Educativa, 2020)
In this paper, the process of elaborating the Municipal Education Plans of two municipalities of São Paulo, Brazil, is analyzed based on the theoretical-methodological perspective of the institutional analysis and the policy cycle approach. It was sought to understand how the subjects directed their actions and carried out the work of elaborating the plans faced with the challenge of meeting national standards without harming local demands. It was verified that, in both municipalities, the subjects followed the official norms of the Federal sphere, giving legitimacy to the process, and, at the same time, they adopted arbitrary strategies of adequacy of the policy text to the context of its systems. It was concluded that the instituted power can act to motivate practices aimed at new ways of doing policies as well as strengthening the use of strategies that reinforce historical centralism in the field of education policy. Keywords: Municipal Education Plans. Institutional Analysis. Policy cycle approach.